Employing contextual-Omni concept towards a sustainable malaysian fashion retail design - Mahusni, Muhammad Nadzrul Adam; Abdul Ghafar, Maszura (Universiti Putra Malaysia Press, 2020)
The rapid changing of information technology application and globalization in the past decade has allured Generation Y’s (Gen Y) to opt for environmentalfriendly and convenient online purchasing to fulfil their shopping needs. The purpose of this study is to identify and employ a potential new concept of Omni–Contextual retail design typology and space programming facilities in Malaysia that could revolutionise the Gen-Y shopping experience. The desktop study investigates on the Gen-Y purchasing behaviour, the Gen Y shopping culture, and retail typologies to distinguish the effectiveness of Omni–Channel and Contextual Retail Design (CRD) in enhancing Gen Y. shopping experience. This study found that interactive omni-channel retail spaces and contextual shopping culture can be the key factors that influence Gen Y ultimate shopping behaviour. The CRD space programming typology would benefit designers in developing better sustainable retail typologies, whilst retailers could gain sustainable business economics especially in Malaysia.